Integrating identity and consumption : an identity investment theory - Thompson, Scott A.; Loveland, James M. (Philadelphia: Taylor and Francis, 2015)
The question of how identity influences consumption behavior has moved to the forefront of marketing research. In addressing this question, research has borrowed disparate theoretical frameworks from other disciplines, impairing the ability to understand phenomena unique to marketing$1 (Bparticularly the active role consumers play in choosing and shaping identities and the reciprocal effects of these choices on consumption. This article proposes Identity Investment Theory (IIT), which treats individuals as deliberate actors making identity-focused consumption choices to receive the greatest return. This theory integrates key elements of several existing theories into a parsimonious framework, providing new insights into important marketing phenomena.s
Keywords: Consumer behaviour -- Personality psychology -- Theory